A novel index including SNPs for the screening of nonalcoholic fatty liver disease among elder Chinese: A population-based study. Issue 13 (March 2018) - Yang, Huanhuan; Chen, Guochong; Song, Chunli; Li, Deming; Ma, Qinghua; Chen, Guangliang; Li, Xinli
Abstract : Abstract: Presently noninvasive methods were employed to the diagnosis of nonalcoholic fatty liver disease (NAFLD), including fatty liver index (FLI), hepatic steatosis index (HSI), product of fasting triglyceride and glucose levels (TyG), and single nucleotide polymorphism (SNP), whereas the accuracy of those indexes need to be improved. Our study aimed to investigate the feasibility of a new index comprehensive index (CI), consisting of 6 serum biomarkers and anthropometric parameters through multivariate logistic regression analysis, to the earlier detection of NAFLD, and the diagnostic value of 5 SNPs (S1: rs2854116 of apolipoprotein C3 [ APOC3 ], S2: rs4149267 of ATP-binding cassette transporter [ ABCA1 ], S3: rs13702 of lipoprotein lipase [ LPL ], S4: rs738409 of protein 3 [patatin-like phospholipase domain containing protein 3 ( PNPLA3 )], S5: rs780094 of glucokinase regulatory protein gene [ GCKR ]) for NAFLD were also explored. Area under the receiver operating characteristic curves (AUROC) and Youden index (YI) were calculated to assess the diagnostic value. The AUROC of CI was higher than FLI, HSI, and TyG (CI: 0.897, FLI: 0.873, HSI: 0.855, TyG: 0.793). Therefore, CI might be a better index for the diagnosis of NAFLD. Although there had no statistical significance ( P = .123), the AUROC and YI were increased when CI combined with rs2854116 (S1) (AUROC = 0.902, YI = 0.6844). The combination of CI with S1 showed even better diagnostic accuracy than CI, which suggests the potential value of rs2854116 for the diagnosis of NAFLD.